THE EFFECT OF SONGS TO THE STUDENTS’ RECOUNT TEXT WRITING QUANTITY (An Experiment at the Second Semester Class A of English Education Students Unib) - Risma Nurandini (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
This study tries to find whether or not song can improve the students’ recount text writingquantity. This quantity means the total of word that was used in a text. The population of theresearch was the second semester English Education students Unib class A that was 38students. The class was divided into two groups (group 1 and group 2). The sample was thegroup 1 as the experimental group and the group 2 as the comparison for the experimentalgroup. The instrument was a writing text. The pre-test was done to find the quality of bothgroups. In the pre test result, it was found that Tcount was 0,36 while Ttable is 2,093. Its meanwas there is no significant difference between the groups. By this result, any group could bedecided which one as control group or experimental group. After the treatments were done onexperimental group and the conventional method on control group, the post-test could be done.Based on the analysis of the post-test, the Tcount (4,85) was higher that Ttable (2,093). It couldbe concluded that the experiment was successful because of song can improve the student’srecount text writing quantity